Seismic vulnerability assessment of a hospital building with and without retrofitting using RC shear walls - Fauzan; Aryo Agista Geby; Syandriaji Diva; Al Jauhari Zev; Bima Suwarso Deara (E3S Web of Conferences)
Revisions to building regulations in Indonesia necessitate assessing building structures, especially hospital buildings. A structural assessment using the current building codes and vulnerability analysis is necessary to ensure the building’s strength against the working loads. In this study, an assessment of the Third-Class Inpatient Building at the Sijunjung Regional General Hospital was carried out using the finite element method (ETABS V21). The structural assessment of the existing hospital building revealed that the inter-story drift values exceed the drift limit, and column and beam structural elements cannot withstand the working loads. The recommendation for retrofitting the building structure is to add RC shear walls to the existing building. The retrofitted building shows an increase in its structural capacity, and the inter-story drift and the strength of the structural elements have met the requirements based on the current Indonesian building codes. Furthermore, structural fragility curves of the hospital building were developed with and without retrofitting against earthquake loads. The vulnerability analysis results indicated that retrofitting the hospital building with shear walls reduces the probability of building damage due to earthquake loads by 52.69% at the level of extensive damage at a PGA of 0.60 g.